Adding more fuel to the fire: an eye-tracking study of idiom processing by native and non-native speaker - Siyanova-Chanturia, Anna; Conklin, Kathy; Schmitt, Norbert (SAGE Publications, 2011)
Using eye-tracking, we investigate on-line processing of idioms in a biasing story context by native and non-native speakers of English. The stimuli are idioms used figuratively (at the end of the day – ‘eventually’), literally (at the end of the day – ‘in the evening’), and novel phrases (at the end of the war). Native speaker results indicate a processing advantage for idioms over novel phrases, as evidenced by fewer and shorter fixations. Further, no processing advantage is found for figurative idiom uses over literal ones in a full idiom analysis or in a recognition point analysis. Contrary to native speaker results, non-native findings suggest that L2 speakers process idioms at a similar speed to novel phrases. Further, figurative uses are processed more slowly than literal ones. Importantly, the recognition point analysis allows us to establish where non-natives slow down when processing the figurative meaning.